Pelatihan dan Pengembangan Karyawan Terhadap Peningkatan Kinerja Karyawan - Ezzah Nahrisah; Tahura, Tengku Lyza; Nila Lestari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
The implementation of training and development programs should have various benefits for long-term careerdevelopment helping employees to accept future tasks and responsibilities. The research method used is a quantitative approach, the type of research is explanatory research. The populat ion is employees of the Madani Medan hotel sample purposive sampling method, namely employees involved in training and development programs. The data collection technique is using the questionnaire method. The results of the study showed that training did not have a significant effect on employee performance. Employee development has a significant effect on employee performance. R Square for y (employee performance) is 0.425. This means that 42.5% of employees work variable (Y) is influenced by variables X1 (training) and X2 (employee development) and the balance is 57.5% determined by other variables outside of research contribution. This research has a high urgency because it can provide useful insights for both HR practitioners, companies and academics i n understanding the relationship between employee training and development and employee performance. The results of this study are expected to be used as a reference in designing more effective and efficient policies that will ultimately improve employee p erformance and the company's competitiveness in an increasingly competitive market.